PACAP and VIP regulate hypoxia-inducible factors in neuroblastoma cells exposed to hypoxia. (June 2018) - Maugeri, Grazia; D'Amico, Agata Grazia; Rasà, Daniela Maria; Saccone, Salvatore; Federico, Concetta; Cavallaro, Sebastiano; D'Agata, Velia
Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) and vasoactive intestinal peptide (VIP) are two related peptides acting as neurotransmitters/neuromodulators in central and peripheral nervous system. They are also involved in cancer showing a controversial role. Particulary, they are implicated in neuroblastoma differentiation (NB). This pediatric tumor can evolve to a malignant metastatic disease or spontaneously regress towards a benign form, known as ganglioneuroblastoma/ganglioneuroma. A negative hallmark of neoplasia progression is represented by hypoxic microenvironment. Low oxygen tension induces activation of hypoxia-inducible factors (HIFs) promoting cells proliferation and metastasis formation. Moreover, HIFs trigger vascular endothelial growth factor (VEGF) release favouring high-risk NB phenotype development. In the present work, we have investigated for the first time, if PACAP and VIP interfere with NB differentiation through modulation of hypoxic/angiogenic process. To this end, we analyzed their effect in malignant undifferentiated and all-trans retinoic acid (RA) differentiated SH-SY5Y cells, representing the benign form of this tumor. Our results have suggested tha both peptides, but predominantly VIP, induce NB differentiation into benign form by regulating HIFs, VEGF and VEGFRs expression and distribution. All these data give new insight regarding PACAP/VIP regulatory role in NB progression. Highlights: PACAP, VIP and their receptors are differentially expressed in neuroblastoma cells. PACAP and VIP modulate the expression of HIFs during hypoxia both in undifferentiated and RA-differentiated cells. Both peptides significantly affect VEGF, VEGFR-1 and VEGFR-2 levels both in undifferentiated and RA differentiated cells. PACAP and VIP may induce NB cells to differentiation in less malignant form through modulation of HIFs/VEGF system.